SHE’RIYATDA UNDALMALAR TAKRORI ORQALI KONNOTATSIYANING IFODALANISHI (Eshqobil Shukur she’rlari misolida) - Rahmatova, S. (SCIENCE and SOCIETY, 2024)
Currently, the issue of expression of connotation is being researched in various aspects in linguistics of the whole world. Considerable work has also been done on the research of reflective means of connotative meanings in poetry. In the artistic text, the pragmatic essence of connotation is manifested in a unique way. This article talks about repetition, which serves to express different connotative meanings in poetics, and the importance of syntactic repetitions used in the poems of the famous Uzbek poet Eshqobil Shukur in expanding the scope of the artistic text. «»